Genome-wide association study of liver-related enzymes suggests putative pleiotropic effects on diverse traits and diseases - Kim, Hyun Seok (2021)
Over the last decade, genome-wide association studies (GWAS) have allowed for the dissection of the genetic susceptibility to complex liver diseases.(1) In a recent issue of Nature communications, Chen et al. conducted a meta-analysis of GWAS collected in approximately 390,000 individuals of the UK BioBank and about 160,000 Japanese individuals from the BioBank Japan, to expand the understanding of the genetic determinants of serum levels of liver-related enzymes.(2) They identified 378 independent loci associated with serum concentrations of alanine aminotransferase (ALT), aspartate aminotransferase (AST), and alkaline phosphatase (ALP). They found several associations of susceptibility loci potentially affecting the level of these enzymes with different traits (pleiotropism), including liver (e.g., steatosis) and non-liver (e.g., ulcerative colitis) diseases. They concluded that these associations were likely not causal, but they provided hypothesis-generating results that can open up avenues of new research.